Business study mission to Mexico : telecommunications - Liew, Rosalind Pieak Yoke (2008)
Mexico is one of the first few countries in Latin America to liberalise its telecommunications market. The Mexican government started re-structuring the telecommunications industry in the late 1980s, to prepare the industry for the eventual opening of the market to foreign competition under the North American Free Trade Agreement (NAFTA) arrangement. The state-owned telecommunications monopoly, Telefonos de Mexico (Telmex), was privatised in 1990. The Federal Telecommunications Law was enacted in 1995 which allowed up to 49% foreign ownership in firms providing most telecommunications services. Many licences have been issued since to local and foreign players for various telecommunications services. The long distance market was liberalised in 1997 - a key milestone in Mexico.